Pendampingan Sistem Informasi Desa Berbasis Internet di Desa Laikaaha Kecamatan Ranomeeto Konawe Selatan - Lina Lestari; Viska Inda Variani; La Ode Rusman; Sapto Raharjo; Ashari Midana (Syntax Corporation Indonesia, 2024)
Laikaaha Village, Ranomeeto District, is one of the villages in South Konawe, Southeast Sulawesi which has diversity in social life. This diversity consists of economic capacity, education, resilience and health which provides its own challenges for the Village Government to develop village development programs. Determining village policies or preparing village programs is very dependent on accurate data, so managing village data and information is very important. Apart from that, the use of an internet-based information system is one of the facilities that can help the Village Government in implementing village programs. Currently, data traffic always moves fast, so assistance is provided with the management of internet-based information systems to produce reliable human resources to manage it. The output of this activity is to increase the capacity of village information system managers so that information system utilization can be maximized. In this activity, the community as users is also involved, and assistance has been provided on how to utilize the existence of the information system. The aim of this community service activity plan is that the Laikaaha Village community has knowledge about the use of information systems, information system managers can improve their skills, the Village Government can make policies and develop programs that are more precise and faster.